(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The study aimed to calculate competitiveness in the Iraqi imports market among main exporters of wheat and rice during (2000-2021). Therefore, some competitiveness indicators were measured, such as revealed comparative advantage, price competitiveness, and market share, in order to determine the market share and competitiveness of the countries exporting the two crops and the extent of their impact on prices. Firstly, the results indicated that Thailand, India, and Pakistan have a revealed comparative advantage in exporting rice to the world, with the exception of the United States of America. Russia has a comparative advantage in exporting wheat to the world better than United States, Canada, and Australia. Secondly, the price competitiveness results for rice showed that both Thailand and Pakistan have price competition in exporting rice with the rest of their competing countries inside Iraq. The price competitiveness for wheat showed that the United States, Canada and Australia have price competitiveness, except for Russia. Finally, the results of the market share of rice and wheat exporters inside Iraq showed that Thailand has the highest market share in exporting rice to Iraq and that the United States has a greater market share in exporting wheat to Iraq.